Two indel variants of prolactin receptor (PRLR) gene are associated with growth traits in goat. Issue 4 (3rd July 2020) - Liu, Xinfeng; Ma, Lin; Wang, Min; Wang, Ke; Li, Jie; Yan, Hailong; Zhu, Haijing; Lan, Xianyong
Abstract: Prolactin receptor ( PRLR ) gene plays a crucial role in the milk production, reproduction and the growth of mammals. To fully characterize the structure of the mutation and to further study the function of the goat PRLR gene, two insertion/deletion (indel) loci (12 bp; 16-bp; 5-bp) were detected in 1038 Shaanbei white cashmere (SBWC) goats. Associated analysis revealed that the 16-bp indel mutation was significantly associated the body length, body height, chest depth (CD), body length index (BLI), heart girth index and cannon circumference index (CCI) ( p  < 0.05). The polymorphism of 5-bp indel was significantly associated with CD, heart girth, CCI and BLI ( p  < 0.05). Overall, individuals with genotype DD showed better phenotypic traits than individuals with other genotypes at the two loci of PRLR gene in SBWC goat. These findings suggested that the two novel indels within the caprine PRLR gene could be considered as effective DNA molecular markers and could provide a valuable theoretical basis for the application of marker-assisted selection in the goat industry.